Denys Dmytrovych Bitchuk - UAOT, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article deals with the 75th anniversary of the birthday of a talented scientist, outstanding orthopaedists-traumatologists, Professor Bitchuk D. D.